Gender and Religion in Central and Eastern Europe: Theoretical approaches - Adamiak, Elżbieta; Sobkowiak, Sonia (European Journal of Mental Health, 2011)
Gender and Religion in Central and Eastern Europe: Theoretical Approaches: Since 1989, Central and Eastern European countries have experienced political and economic changes which have without doubt influenced social life and forced a new appraisal of the roles of men and women. The awareness of sex/gender difference has been examined on many different levels and has become an important part of academic research. In this article, the authors analyse feminist publications from the last twenty years and ask how the idea of gender has influenced religions and religious communities. They investigate how the notion of gender is understood, on what levels it can be explored and how it is present in religion. The article offers an overview of studieson gender awareness in religious teaching and religious communities (including some of new religious movements) in Central and Eastern European countries. Furthermore, it presents the most recent research into the religious influences on social roles of women and how women perceive their roles in society and the Churches. Finally, the authors ask whether the connection between gender and culture includes religious references, where gender, culture and religion meet, and what problems emerge in that meeting specifically with the example of Poland.